2017
DOI: 10.1071/an15776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic Bacillus amyloliquefaciens strain H57 on productivity and the incidence of diarrhoea in dairy calves

Abstract: A spore-forming probiotic, Bacillus amyloliquefaciens strain H57 (H57), was administered to dairy calves in starter pellets to determine effects on liveweight gain, feed conversion efficiency and animal health under summer feeding conditions, without antibiotics. Twenty-four male and female calves were allocated into two groups and from 4 weeks of age individually offered 6 L/day of whole milk and ad libitum starter pellets impregnated with H57 (3.16 × 108 cfu per kg DM) or without (Control) until 12 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 29 publications
2
37
0
1
Order By: Relevance
“…Le et al (2016b), showed that pregnant Dorper ewes fed a poor quality concentrate diet supplemented with H57 at 10 9 cfu kg -1 pellets, had a significant increased weight gain (P = 0.008) coupled with an increase in uptake of dry matter (P = 0.03) and increased nitrogen retention (P = 0.01) compared to the control animals given pellets without H57. The beneficial effect of H57 was also demonstrated in dairy calves (Le et al, 2016a) fed sorghum based concentrate pellets with and without H57 as they weaned. Not only was there a 39% increase in live weight gain, a 16.2% increase in feed conversion efficiency and a reduction in weaning age by nine days, but the H57 fed calves also had a reduction in the occurrence and duration of diarrhoea.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Le et al (2016b), showed that pregnant Dorper ewes fed a poor quality concentrate diet supplemented with H57 at 10 9 cfu kg -1 pellets, had a significant increased weight gain (P = 0.008) coupled with an increase in uptake of dry matter (P = 0.03) and increased nitrogen retention (P = 0.01) compared to the control animals given pellets without H57. The beneficial effect of H57 was also demonstrated in dairy calves (Le et al, 2016a) fed sorghum based concentrate pellets with and without H57 as they weaned. Not only was there a 39% increase in live weight gain, a 16.2% increase in feed conversion efficiency and a reduction in weaning age by nine days, but the H57 fed calves also had a reduction in the occurrence and duration of diarrhoea.…”
Section: Introductionmentioning
confidence: 75%
“…To conclude, the methodology adopted was an effective means of cultivating B. amyloliquefaciens H57 to produce inoculant in sufficient quantities for several tonnes of animal feed at greater than 10 9 cfu kg -1 (Le et al, 2016a;Le et al, 2016b). Inoculum prepared in this manner has been stored for more than a year without loss of viability (Table S2.5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations